S100P and HYAL2 as prognostic markers for patients with triple-negative breast cancer - Maierthaler, Melanie; Kriegsmann, Mark; Peng, Cike; Jauch, Sarah; Szabo, Akos; Wallwiener, Markus; Rom, Joachim; Sohn, Christof; Schneeweiss, Andreas; Sinn, Peter; Yang, Rongxi; Burwinkel, Barbara (Experimental and molecular pathology, 2015)
Triple-negative breast cancer (TNBC) is a group of very aggressive breast tumours, characterised by lack of expression of oestrogen receptor (ER), progesterone receptor (PR) and erb-b2 receptor tyrosine kinase 2 (ERBB2/HER2). Nevertheless, TNBCs show different clinical characteristics and are very diverse regarding prognostic outcome. So far, only a few prognostic markers for TNBC have been reported that could be helpful for therapeutic stratification. Here we have analysed the expression of S100P and HYAL2 using immunohistochemistry (IHC) in a TNBC cohort of 98 patients with a follow-up for recurrence and death. TNBC patients with high expression of both proteins showed significantly shorter progression-free survival (PFS) (mean PFS = 35.9 months, P = 0.001) compared to TNBC patients with high expression levels of only one of the proteins (mean PFS = 69.4 months) and to TNBC patients with low expression of both proteins (mean PFS = 83.3 months). Moreover, multivariate Cox-regression model showed the combined expression of S100P and HYAL2 as independent prognostic factor for PFS (P = 0.001). The expression of S100P and HYAL2 indicated similar prognostic effect to the overall survival (OS) of TNBC patients. In addition, high expression levels of both S100P and HYAL2 showed significant association with different clinicopathological characteristics, such as more recurrence events (P = 0.004), and higher occurrence of metastasis (P = 0.002). Our study proposes S100P and HYAL2 as potential prognostic markers for TNBC.